2019
DOI: 10.1002/anie.201814243
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Imine Cages into Hydrocarbon Cages

Abstract: In contrast to organic cages which are formed by exploiting dynamic covalent chemistry, such as boronic ester cages, imine cages, or disulfide cages, those with a fully carbonaceous backbone are rarer. With the exception of alkyne metathesis based approaches, the vast majority of hydrocarbon cages need to be synthesized by kinetically controlled bond formation. This strategy implies a multiple step synthesis and no correction mechanism in the final macrocyclization step, both of which are responsible for low o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…[10][11][12][13][14] Furthermore,cages offer synthetic handles that can be used to finely tune their cavity shape and electronic properties,a nd hence potential interactions with guest molecules. [7,[15][16][17][18][19] However, the synthesis of molecular cages is often challenging,p articularly where multiple bonds must be formed selectively.T oavoid this problem, many molecular cage syntheses take advantage of dynamic covalent chemistry, in which reversible reactions provide an error correction mechanism to ensure the thermodynamic cage product is obtained. [20][21][22] In the case of imine-based cages,m ultiple amines and aldehydes must react to yield asingle cage species instead of oligomeric mixtures of imines.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Furthermore,cages offer synthetic handles that can be used to finely tune their cavity shape and electronic properties,a nd hence potential interactions with guest molecules. [7,[15][16][17][18][19] However, the synthesis of molecular cages is often challenging,p articularly where multiple bonds must be formed selectively.T oavoid this problem, many molecular cage syntheses take advantage of dynamic covalent chemistry, in which reversible reactions provide an error correction mechanism to ensure the thermodynamic cage product is obtained. [20][21][22] In the case of imine-based cages,m ultiple amines and aldehydes must react to yield asingle cage species instead of oligomeric mixtures of imines.…”
Section: Introductionmentioning
confidence: 99%
“…10B). 81 This widespread pre-orientation strategy is dependent on four prerequisites (Fig. 11): The reversible assembly does not disassemble under the conditions of the stability inducing step; the building blocks are oriented correctly to allow the reaction to occur; the order in the material needs to withstand forces generated during or because of the transformation; the reagents and catalysts need to reach the COF linkage and need to be able to perform the reaction irrespective of the sterically challenging environment.…”
Section: Figmentioning
confidence: 99%
“…[263] Mastalerz et al reported that an imine-based POC could be chemically transformed into hydrocarbon cage, using a three-step method: imine reduction, nitrosylation with isoamyl nitrite, and Overberger rearrangement. [264] Using different chemistry, Yamago et al reported a carbon-based nanocage, which was prepared by postsynthetically modifying a platinum nanocage, via reductive elimination of the platinum (Figure 11). [228] Itami et al, and others, have reported a series of carbon-based nanocages, which were prepared by postsynthetically aromatizing cyclohexane moieties under acidic conditions, [225,226,265] and related reductive aromatization reactions.…”
Section: Postsynthetic Modification Of Porous Organic Cagesmentioning
confidence: 99%